1975
DOI: 10.1037/h0076784
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of experienced sexual arousal in response to erotic stimuli through misattribution of unrelated residual excitation.

Abstract: In a pretest, three phases of recovery from a standard physical exercise were determined. In Phase 1, subjects experienced high levels of physiological excitation and recognized that their arousal was due to exercise. In Phase 2, subjects maintained substantial excitatory residues from the exercise but felt that their arousal had returned to base level. In Phase 3, subjects' excitatory responses had decayed, and they knew they had recovered from the exercise. Subjects in the main experiment were exposed to an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
2

Year Published

1979
1979
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(107 citation statements)
references
References 6 publications
4
101
2
Order By: Relevance
“…In our experiments, we examined a relatively narrow slice of the taxonomic pie, finding that the type of positive affect manipulated (incidental vs. integral, and relatively feeling vs. thinking based) appears to make little difference on processing effects, relative to the influence of affect valence. This, however, may not be sur-prising given individuals' inability to accurately detect the source of their affective states (e.g., Cantor, Zillmann, and Bryant 1975;Dutton and Aron 1974;Schwarz and Clore 1983). Individuals are especially likely to be unaware (and misattribute) the source of their affective arousal when the arousal source is not salient and when the arousal itself is relatively moderate (Gorn, Pham, and Sin 2001;Payne et al 2010;Vosgerau 2010).…”
Section: Discussionmentioning
confidence: 98%
“…In our experiments, we examined a relatively narrow slice of the taxonomic pie, finding that the type of positive affect manipulated (incidental vs. integral, and relatively feeling vs. thinking based) appears to make little difference on processing effects, relative to the influence of affect valence. This, however, may not be sur-prising given individuals' inability to accurately detect the source of their affective states (e.g., Cantor, Zillmann, and Bryant 1975;Dutton and Aron 1974;Schwarz and Clore 1983). Individuals are especially likely to be unaware (and misattribute) the source of their affective arousal when the arousal source is not salient and when the arousal itself is relatively moderate (Gorn, Pham, and Sin 2001;Payne et al 2010;Vosgerau 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Other studies have shown the ability for physiologicallyarousing video segments to intensify emotional responses to mediated (Zillmann, Mody, & Cantor, 1974) or non-mediated stimuli (Cantor, Zillmann, & Einsiedel, 1978). In addition, increased arousal from physical exercise has resulted in higher ratings of arousal and enjoyment of later media content (Cantor, Zillmann, & Bryant, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Arousal decays relatively slowly (e.g., Cantor, Zillmann, & Bryant, 1975). As a result, the residual arousal experienced following an event may polarize the response to a subsequent target by intensifying the affect elicited by this target.…”
Section: Arousal and Polarizationmentioning
confidence: 99%
“…According to the excitation transfer hypothesis (e.g., Cantor et al, 1975;Zillmann, 1971), high arousal should polarize subsequent ad evaluations if consumers believe that the context-induced arousal reflects their genuine affective reactions to the ad itself. Consumers inspecting "how they feel" about an ad (e.g., Pham, 1998;Schwarz & Clore, 1988) may infer from their arousal that they "feel strongly" about the ad and hence evaluate it more extremely.…”
Section: Studymentioning
confidence: 99%